Roadmap for Implementation of Building Information Modelling in the Construction Industry in Sudan (Journal of Building and Road Research, 2022)
The importance of the building information modelling (BIM) adoption has been increasingly recognized by the construction industry in Sudan and all over the world. It is facing many barriers and challenges to increaseproductivity, efficiency, and quality. This paper aims to develop a roadmap to facilitate BIM implementation in Sudan and to ensure a smooth transition from traditional working methods to BIM technology focusing on three factors: technology, process, and people. The developed concept map and roadmap in the paper give tools and guidelines for assessment of theorganisation by identifying key challenges and actions to be considered in order to implement BIM in Sudan.
Keywords: BIM; Construction industry; Implementation; Roadmap; Concept map